ANALYSIS OF TOURISM VILLAGES DEVELOMPENT IN INDONESIA: CASE STUDIES : THREE TOURISM VILLAGES - Latif, Aqilah Nurul Khaerani (ASEAN Journal on Hospitality and Tourism, 2018)
Potential tourist resources that attract many visitors are in the countryside, where natural resource potential is the main attraction. This has encouraged a number of countries to start upgrading villages to support tourism. Although physical investment is seen as accelerating tourism development, tourism sustainability in an area is not going well without the participation of the local community. This paper discusses the development of rural tourism in Indonesia. There are three tourism villages representing the Indonesian Tourism Village, namely Kampung Naga in Tasikmalaya Regency, Sinarresmi Tradisional Village in Sukabumi Regency (Ciletuh Geopark area), and Sade Village in Central Lombok Regency. The background includes the tourism component (attractions, facilities, and accessibility) and community resilience and tourism market segmentation to changes in regional functions. Methodology includes literature review and observation. The findings of this study indicate that the development of sustainable tourism in rural areas is strongly influenced by community acceptance and resilience in tourism development. As in Kampung Naga and Kampung SInarresmi consider the village is not a tourist attraction, the visit that comes not as an opportunity, but their reception as hosts and tourists as guests. Meanwhile, in Sade Village consider their area as a tourist attraction, so that tourist visits are seen as opportunities for economic growth, by commercializing traditional dances.